Risk communication and miscommunication: case studies in science, technology, engineering, government and community organizations - Boiarsky, Carolyn R., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2016)
Boiarsky draws from research in rhetoric, linguistics, technical communication, and psychology for a new approach at risk communication and the communication skills necessary for dealing with environmental and technological problems that could lead to major crises.--Provided by publisher.
Chapter 1. Writing and Reading in the Context of the Environmental Sciences: A Case Study of the Chicago Flood. Introduction -- The Chicago Flood -- Reading Koncza's Memo -- Knowledge of the Topic Affects the Reader's Comprehension of the Message -- Recognizing the Purpose of a Message Affects the Reader's Response to a Message -- The Context in Which a Reader Reads a Document Affects the Reader's Interpretation of the Message -- Readers' Reading Styles and Patterns Determine the Information Readers Obtain -- Writing a More Effective Memorandum -- Summary: What Readers Do -- Chapter 2. Effective Discourse Strategies: A Case Study of the 2011 Mississippi Flood -- Introduction -- The 2011 Mississippi Flood -- Writing the Corps's Letters: Making Appropriate Rhetorical Decisions. Focusing on the Readers' as Well as the Writers' Purposes -- Providing Content Readers Want and Need -- Organizing Information to Facilitate Readers' Comprehension -- Helping Readers Read Fluently -- Summary -- Chapter 3. Effective Persuasive Strategies: Cheap, Available Coal Power vs. a Clean Environment. Introduction Continued Use of Coal as a Source of Energy -- Recognizing Readers' Biases. Reflecting Readers' Attitudes -- Reflecting Readers' Concept of Valid Evidence -- Helping Readers Follow a Line of Reasoning -- Review -- Chapter 4. Communicating with Electronic Media: Case Studies in the Columbia Shuttle Breakup and the BP/Horizon Oil Rig Explosion. Communicating via Electronic Media -- Reading on Electronic Media -- Columbia Shuttle Accident -- Writing for Electronic Media -- The BP/Horizon Gulf Oil Rig Explosion -- Problems in Communicating with Electronic Media -- 1. Transfer of the Conventions and Style of Social Media to Technical/Scientific Correspondence -- 2. Transfer of the Functions of the Telephone to E-mail and Text Messages -- 3. Sole Reliance on Electronic Media to Discuss Complex Messages -- 4. Failure to Read, Reflect on, and Revise a Draft -- Conclusion -- Recommendations for Writing Effective Electronic Messages -- Chapter 5. Communicating with PowerPoint: The Army, NASA, and the Enbridge Pipeline. PowerPoint and the Army -- Inappropriate Rhetorical Decisions -- Columbia Shuttle Breakup -- Inappropriate Graphical Decisions -- Synergistic Effects Differentiating Effects between Textual and Graphical Slides -- Effects of a Slide Deck -- Effects of Handouts and Note-Taking -- Improving Presentations -- Changing Perspective -- Reducing Synergistic Effects -- Guidelines -- Slides -- Handouts and Note-Taking -- An Effective Slideware Presentation Mixing Graphics and Text: Expansion of the Enbridge Pipeline -- Example of a Presentation with Text-Based Slideware.
Keywords: Risk communication; Miscommunication